PEMAHAMAN KONSUMSI ISLAM, KEMUDAHAN MENGAKSES DAN PROMOSI TERHADAP PEMBELIAN IMPULSIF MAHASISWA MUSLIM PADA SHOPEE - NAJMA NABIELA (Islamic Economics and finance in Focus, 2023)
The high level of smartphone ownership is used by the public to use online apps for transactions. This study aims to see the effect of understanding consumption in an Islamic view, ease of accessing applications and promotions on impulse purchases. The analytical method used is descriptive quantitative method. The research location in Malang City uses a Likert scale. The questionnaire used purposive sampling and was distributed to the 5 best universities in Malang City. Analyzed using descriptive statistical analysis, validity test, reliability test, classic assumption test, multiple regression analysis and hypothesis testing using the SPSS 21 program. The results of this study indicate that understanding of Islamic consumption has a negative and significant effect on the impulsive buying of Malang City Muslim students on the Shopee marketplace . Meanwhile, the ease of access and promotion had a positive and significant effect on the impulsive purchases of Malang City Muslim students on the Shopee marketplace. This research becomes information material for the public, especially Muslim communities, to stay away from israf and comply with Islamic teachings in making purchasing decisions.